Network analysis and synthesis - Pandey, O.N (Ane Books, 2014)
This is the basic textbook for undergraduate students of engineering. The book is as per the prescribed syllabus of Network Analysis and Synthesis in universities of India and abroad. It explains the Fundamentals of engineering, signals for analysis, DC circuits and AC circuits, graph theory, network theorems, network functions, two port networks, network synthesis and filters.